Nanoporous Activated Carbons Derived from Peach Stones - Jha, Abhimanyu; Mallick, Aabhash K.; Shrestha, Rajeshwar M.; Joshi, Rinita Rajbhandari (Journal of the Institute of Engineering, 2020)
In this work, nanoporous activated carbons from Peach Stone powder was achieved using phosphoric acid as an activating agent and carbonization has been conducted at temperatures ranging from 400oC to 700oC using Nitrogen as inert gas in a tubular furnace, to understand the effect of the adsorption capacity with variation in temperature. Evaluation of microporosity of each of these specimens was performed by Iodine Number technique, of which the results showed a maximum amount of micropores in the carbon at the carbonization temperature of 500oC. The morphology of the carbon samples at two extreme temperatures of 400oC and 700oC was studied using FE-SEM images, which demonstrated large amount of nanoporous in the carbon surfaces at the higher temperature. Raman Spectroscopy outcomes delineate the similar amorphous nature of the carbonaceous specimen at these temperatures with both G band and D band. These results indicate a potential to develop a good adsorbent material applicable for water purification.